Instrumen Hasil Penilaian Afektif Kurikulum 2013 - Lestari, Lestari; Arifah, Husnul; Putri, Fia Alifah (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
Abstrack The assessment is to find out how the assessment instrument on the 2013 curriculum affective learning outcomes. Assessment is very important in the learning process, a good assessment will have a good impact on the lerning process. Affective assessment is an aspect of attitude that is embedded in each student’s personality, the assessment in the affective aspect is one of the three very important aspects in each student’s personality. In the affective aspect is one of the most important aspects of learning in schools. The assessment of the KTSP curriculum to the 2013 curriculum brings new challenges because of the limited ability of teachers’ insight into the assessment system, especially on attitude assessment instruments. The method used in this researce is a qualitative method with the type of literature study with analytical techniques. The results of this study have several levesl in the affective domain. Namely the level of receiving or paying attetion, the level ofresponding, the level of apprecation, the level of organizing and the level of personality or character. Assessment of the affective domain is arranged in the form of a likert scale or a sematic differential scale. A scale is a set of values or numbers assigned to a subject, object or behavior for the purpose of quantification and quality measurement. The scale is used to measure attitudes, values, interests, motivations and so on related to psychological attributes. Assessment instrument on affactive assessment using a non-tes form of assessment. Keyword : curricullum 2013, affective assessment, assessment instrument